2016
DOI: 10.1002/cssc.201501661
|View full text |Cite
|
Sign up to set email alerts
|

Dye‐Sensitized Cu2XSnS4 (X=Zn, Ni, Fe, Co, and Mn) Nanofibers for Efficient Photocatalytic Hydrogen Evolution

Abstract: The photocatalytic hydrogen evolution activities of low-cost and noble-metal-free Cu2 XSnS4 (X=Zn, Ni, Fe, Co, and Mn) nanofiber catalysts have been investigated using triethanolamine as an electron donor and eosin Y as a photosensitizer under visible-light irradiation. The rates of hydrogen evolution by Cu2 XSnS4 (X=Zn, Ni, Fe, Co, and Mn) nanofibers have been compared with each other and with that of the noble metal Pt. The hydrogen evolution rates for the nanofibers change in the order Cu2 NiSnS4 >Cu2 FeSnS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Ga incorporation replacing part of the In allowed adjusting the band gap shifting the CB edge and providing a larger driving force for catalyzing the water splitting reduction reaction . Cu 2 X SnS 4 (where X =Zn, Ni, Fe, Co, and Mn) materials have been also found active in H 2 evolution from water without the need of a co‐catalyst . The presence of Au NPs and the development Au/Cu 2 FeSnS 4 core‐shell nanostructures improved significantly H 2 production, a mechanism that was attributed to the LSPR effect induced by Au NPs …”
Section: Cu‐based Materials For Hydrogen Photocatalytic Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ga incorporation replacing part of the In allowed adjusting the band gap shifting the CB edge and providing a larger driving force for catalyzing the water splitting reduction reaction . Cu 2 X SnS 4 (where X =Zn, Ni, Fe, Co, and Mn) materials have been also found active in H 2 evolution from water without the need of a co‐catalyst . The presence of Au NPs and the development Au/Cu 2 FeSnS 4 core‐shell nanostructures improved significantly H 2 production, a mechanism that was attributed to the LSPR effect induced by Au NPs …”
Section: Cu‐based Materials For Hydrogen Photocatalytic Productionmentioning
confidence: 99%
“…[61] Cu 2 XSnS 4 (where X = Zn, Ni, Fe, Co, and Mn) materials have been also found active in H 2 evolution from water without the need of a co-catalyst. [62] The presence of Au NPs and the development Au/Cu 2 FeSnS 4 core-shell nanostructures improved significantly H 2 production, a mechanism that was attributed to the LSPR effect induced by Au NPs. [53] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 Copper sulfides have been also coupled with other SCs.…”
Section: Copper Chalcogenidesmentioning
confidence: 99%
“…Gonce at el . from the same group has also investigated the photocatalytic hydrogen evolution rates of EY sensitized CM I TS (M I =Zn, Ni, Fe, Co and Mn) nanofibers under similar conditions . The hydrogen evolution rates for the nanofibers change in the order CNTS (2028 μmol g −1 h −1 ) > CCTS (1926 μmol g −1 h −1 ) > CFTS (1870 μmol g −1 h −1 ) > CZTS (1420 μmol g −1 h −1 ) >CMTS (389 μmol g −1 h −1 ).…”
Section: Photoelectrochemical and Photocatalytic Applicationsmentioning
confidence: 99%
“…Furthermore, cobalt and nickel can be co-electrodeposited from a citrate based solution owing to their suitable reduction potential in the Cu-Zn-Sn electrodeposition system as an alternative simple method to dope CZTS films [76,201,202]. Cobalt-containing Cu 2 Co x Zn 1-x SnS 4 and Cu 2 CoSnS 4 materials have been grown as nanofibers and nanorods before [198,203]; however, a low doping amount in CZTS films for the modification of CdS/CZTS band alignment has not been reported as yet. Nickel containing Cu 2 Ni x Zn 1-x SnS 4 and Cu 2 NiSnS 4 materials have been grown as a film, nanofiber and nanorods [198,199,203]; nevertheless none of these studies reported the photoelectrochemical or solar cell performance of these materials.…”
Section: Future Workmentioning
confidence: 99%
“…Cobalt-containing Cu 2 Co x Zn 1-x SnS 4 and Cu 2 CoSnS 4 materials have been grown as nanofibers and nanorods before [198,203]; however, a low doping amount in CZTS films for the modification of CdS/CZTS band alignment has not been reported as yet. Nickel containing Cu 2 Ni x Zn 1-x SnS 4 and Cu 2 NiSnS 4 materials have been grown as a film, nanofiber and nanorods [198,199,203]; nevertheless none of these studies reported the photoelectrochemical or solar cell performance of these materials. Cobalt containing CZTS films can be synthesized via sulfurization of co-electrodeposited Cu-Zn-Sn-Co metallic precursors on Mo substrate with varying compositional ratios for the optimization of band gap as well as band alignment for CdS/CZTS interface.…”
Section: Future Workmentioning
confidence: 99%